Flame-retardant cross-linked irradiation cable material for charging pile liquid-cooled cable and preparation method of flame-retardant cross-linked irradiation cable material
By using methylvinyl silicone rubber, modified glass powder, magnesium hydroxide and modified triphosphazene flame retardant in ceramic silicone rubber, and performing electron beam irradiation crosslinking, the problems of poor flame retardant effect and incomplete ceramic layer in ceramic silicone rubber are solved, and the excellent flame retardant performance and ceramic construction performance of cable materials are achieved.
Patent Information
- Application Number
- CN202411471010.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The compatibility of refractory fillers, fluxes and inorganic fillers in ceramicized silicone rubber leads to poor flame retardant effect and incomplete ceramicized layer.
Methylvinyl silicone rubber is used as the matrix, modified glass powder, magnesium hydroxide and modified triphosphazene flame retardant are added, and cross-linked by electron beam irradiation to form a three-dimensional cross-linking network to improve flame retardant performance and ceramicized construction performance.
It significantly improves the flame retardant performance of the cable material and the denseness of the ceramic layer, and enhances the mechanical properties and high temperature stability of the cable material.
Smart Images

Figure BDA0005094691140000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame retardant cross-linked irradiated cable materials, and in particular to a flame retardant cross-linked irradiated cable material for a charging pile liquid cooling cable and a preparation method thereof. Background Art
[0002] Ceramic silicone rubber fire-resistant cable is a new type of electrical material. When it is eroded by flames, it can form a structurally stable, dense and non-flammable ceramic layer to effectively protect the internal wire core and materials. It is prepared by adding refractory fillers, flux and some other inorganic fillers to the silicone rubber matrix. Ceramic silicone rubber has attracted much attention because of its processability at room temperature and its easy ceramicization at high temperatures. However, due to the poor compatibility of refractory fillers, flux and some other inorganic fillers in ceramic silicone rubber, problems such as poor flame retardant effect and incomplete ceramic layer formed are caused.
[0003] In order to improve the flame retardant properties and ceramic-forming properties of ceramic silicone rubber, it is of great significance to use radiation cross-linking technology to prepare a flame retardant cross-linked irradiated cable material with excellent flame retardant properties and ceramic-forming properties. Summary of the invention
[0004] The object of the present invention is to provide a flame retardant cross-linked irradiated cable material for a charging pile liquid cooling cable and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable comprises the following steps:
[0007] Add methyl vinyl silicone rubber into a mixer and start mixing; add fumed silica, mica powder and hydroxy silicone oil in sequence and mix for 10-30 minutes; add modified glass powder, magnesium hydroxide and modified triphosphazene flame retardant and mix for 10-30 minutes; cold press molding, irradiation cross-linking, and obtain flame-retardant cross-linked irradiated cable material.
[0008] Furthermore, the radiation source for the radiation crosslinking is a cobalt source with a radioactivity of 2.146×10 16 Bq; irradiation dose is 120kGy.
[0009] Furthermore, the proportions of the components in the flame-retardant cross-linked irradiated cable material, by mass, are 100-120 parts of methyl vinyl silicone rubber, 15-20 parts of fumed silica, 30-40 parts of mica powder, 2.5-3 parts of hydroxy silicone oil, 20-30 parts of modified glass powder, 1-10 parts of magnesium hydroxide, and 1-10 parts of modified triphosphazene flame retardant.
[0010] Furthermore, the method for preparing the modified glass powder comprises the following steps:
[0011] S1: mixing phosphate glass powder and cerium oxide uniformly, compacting, and placing in a muffle furnace for high-temperature calcination to obtain a composite glass block; crushing the composite glass block, sieving, ball milling, and sieving again to obtain a composite glass powder;
[0012] S2: adding dimethyl monochlorosilane, vinyl trichlorosilane, chloroplatinic acid and deionized water to ether, heating for reaction, removing ether and water by vacuuming under reduced pressure, adding acrylic acid, and keeping the temperature for reaction under nitrogen atmosphere to obtain carboxyl-terminated hyperbranched polysiloxane;
[0013] S3: uniformly mixing the carboxyl-terminated hyperbranched polysiloxane, urea and antimony trioxide, heating for vacuum reaction, heating for normal pressure reaction, and cooling to obtain an amide-terminated hyperbranched polysiloxane;
[0014] S4: After the surface of the composite glass powder is acidified, it is ultrasonically dispersed in ether, and terminal amide hyperbranched polysiloxane is added. The reaction is stirred, washed, and dried. The dried product is added to chloroplatinic acid ether solution, stirred evenly, and the ether is removed by rotary evaporation to obtain modified glass powder.
[0015] Furthermore, in step S1, the mass ratio of phosphate glass powder: cerium oxide is (18-19): (1-2); the high-temperature calcination step is to heat the temperature to 1000-1020°C at a rate of 8-10°C / min and keep warm for 30-45min; the screening is a 10-20 mesh sieve; the ball milling rate is 420-450rpm, and the ball milling time is 5-6h; the secondary screening is a 200-300 mesh sieve.
[0016] Furthermore, in step S2, the mass ratio of dimethyl monochlorosilane: vinyl trichlorosilane: acrylic acid is (18-20): (1.1-1.3): (13-15); the heating reaction temperature is 40-50°C, and the heating reaction time is 4-6h; the reduced pressure vacuum temperature is 120-150°C; the insulation reaction temperature is 120-150°C, and the insulation reaction time is 4-6h.
[0017] Furthermore, in the step S3, the mass ratio of the terminal carboxyl hyperbranched polysiloxane: urea is 6:(5-10); the heating vacuum reaction temperature is 145-150°C, the vacuum degree is 0.09-0.1MPa, and the reaction time is 1-1.5h; the heating normal pressure reaction step is to increase the temperature to 165-170°C, 185-190°C, 205-210°C, 225-230°C at a rate of 4-5°C / min, and keep warm for 30-45min, 30-45min, 30-45min, and 2-2.5h, respectively.
[0018] Furthermore, in step S4, the mass ratio of the composite glass powder: the amide-terminated hyperbranched polysiloxane: the chloroplatinic acid in the chloroplatinic acid ether solution is 1:(1-2):(0.15-0.34).
[0019] Furthermore, the preparation method of the modified triphosphazene flame retardant comprises the following steps:
[0020] 4-ethoxyphenol, hexachlorocyclotriphosphazene and sodium hydroxide are added to tetrahydrofuran, and refluxed to obtain a cyclophosphazene p-ethoxyphenol derivative; the cyclophosphazene p-ethoxyphenol derivative is added to a dichloromethane solution of boron tribromide, and reacted at room temperature to obtain a cyclophosphazene p-hydroxyphenol derivative; the cyclophosphazene p-hydroxyphenol derivative, allyl bromide and potassium carbonate are added to acetone, and refluxed to obtain the solvent, and the solvent is removed under reduced pressure, washed and dried to obtain a modified triphosphazene flame retardant.
[0021] Furthermore, in the cyclophosphazene p-ethoxyphenol derivative, the mass ratio of 4-ethoxyphenol: hexachlorocyclotriphosphazene: sodium hydroxide is 1:(2.5-2.58):(0.98-1.02); in the cyclophosphazene p-hydroxyphenol derivative, the mass ratio of cyclophosphazene p-ethoxyphenol derivative: boron tribromide is (2.2-2.28):(1.64-1.7); in the modified triphosphazene flame retardant, the mass ratio of cyclophosphazene p-hydroxyphenol derivative: allyl bromide: potassium carbonate is (0.8-0.89):(0.72-0.74):(0.84-0.85).
[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0023] In the conventional scheme of the present invention, polyethylene is used as the matrix material of the cross-linked irradiated cable material. It is an insulating material with excellent electrical properties at room temperature. It is cross-linked by irradiation to change its molecular structure from the original linear structure to a three-dimensional mesh structure. It has excellent mechanical and electrical properties and is widely used in the field of cable materials. On this basis, in order to further optimize the performance, the present invention uses methyl vinyl silicone rubber as the matrix material of the cross-linked irradiated cable material to further improve the mechanical properties of the irradiated cross-linked cable material.
[0024] The present invention uses 4-ethoxyphenol, hexachlorocyclotriphosphazene and allyl bromide as main raw materials to prepare a functionalized modified triphosphazene flame retardant containing terminal allyl groups; the flame retardant is added to a silicone rubber matrix, and under the action of electron beam irradiation cross-linking, the allyl group with unsaturated double bonds in the methyl vinyl silicone rubber is irradiated by the electron beam, and forms a three-dimensional cross-linked network with the allyl group in the modified triphosphazene flame retardant through a free radical cross-linking reaction, which provides flame retardant properties and also has a sensitizing effect, thereby increasing the gel content in the cable material, increasing the residual amount of the cable material at high temperature, and being conducive to participating in the construction of a ceramic layer. On the one hand, the cross-linking density of the silicone rubber matrix is increased, and the overall mechanical properties of the cable material are enhanced. On the other hand, the N and P elements in the modified triphosphazene flame retardant can be evenly distributed in the cable material, further improving the ceramic construction performance and flame retardant performance of the cable material.
[0025] In order to further improve the ceramic construction performance and flame retardant performance of cable materials, while improving or maintaining the mechanical properties of cable materials as much as possible; the present invention uses low-melting point phosphate glass powder as the main raw material, introduces rare earth oxide of cerium for calcination, grinds, and prepares composite glass powder; introducing cerium oxide into phosphate glass powder, on the one hand, can improve the hardness of glass, help to improve the overall strength of the ceramic layer, have a lower volume change rate after calcination at 1000°C, improve the ceramic density of cable materials, and have excellent ceramic performance; on the other hand, as a synergistic flame retardant, it is combined with a modified triphosphazene flame retardant to further improve the flame retardant performance of the cable material.
[0026] Next, terminal carboxyl hyperbranched polysiloxane is reacted with urea through an amidation reaction to prepare terminal amide hyperbranched polysiloxane; terminal amide hyperbranched polysiloxane and the acidified composite glass powder are self-assembled through electrostatic adsorption to form terminal amide hyperbranched polysiloxane modified composite glass powder; finally, the unshared electrons on the amide group are used to form a complex with metal Pt to prepare modified glass powder; Pt catalyst is introduced into the surface of the composite glass powder through the terminal amide hyperbranched polysiloxane, on the one hand, it can inhibit the generation of low molecular weight cyclic polysilane and depolymerizable transition complex, and achieve the purpose of enhancing the ceramic effect; on the other hand, using the composite glass powder as a carrier greatly enhances its dispersion performance in the cable material, achieves the purpose of stabilizing part of the condensation product, promotes the growth of the insulating ceramic layer, greatly improves the density of the ceramic layer, and further improves the flame retardant performance of the cable material. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the following examples, methyl vinyl silicone rubber Mn = 450000-550000, vinyl content is about 1.6%, purchased from Dow Corning; mica powder was purchased from Xuzhou Jinya Powder Co., Ltd.; fumed silica specific surface area: 120±15m 2 / g, with a particle size of about 14nm, purchased from Cabot Corporation; hydroxy silicone oil was purchased from Qingdao Fenghong Chemical Co., Ltd.; the chemical composition of the glass powder is 41% P2O5, 21.5% Al2O3, 17.4% Na2O, 15.4% K2O, 0.8% SiO2, 0.8% CaO, purchased from Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.; the remaining raw materials are commercially available.
[0029] The preparation method of the modified triphosphazene flame retardant comprises the following steps:
[0030] 1g 4-ethoxyphenol, 2.5g hexachlorocyclotriphosphazene, and 0.98g sodium hydroxide are added to 25mL tetrahydrofuran, and refluxed to obtain a cyclophosphazene p-ethoxyphenol derivative; 2.2g cyclophosphazene p-ethoxyphenol derivative and 1.64g boron tribromide are added to 30mL dichloromethane, and reacted at room temperature to obtain a cyclophosphazene p-hydroxyphenol derivative; 0.8g cyclophosphazene p-hydroxyphenol derivative, 0.72g allyl bromide, and 0.84g potassium carbonate are added to 30mL acetone, and refluxed to react, and the solvent is removed by evaporation under reduced pressure, washed, and dried to obtain a modified triphosphazene flame retardant.
[0031] Example 1: A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid-cooled cable: S1: 18 g of phosphate glass powder and 2 g of cerium oxide were mixed evenly and compacted, and then placed in a muffle furnace and heated to 1000°C at a heating rate of 10°C / min and calcined at a high temperature for 30 min to obtain a composite glass block; after the composite glass block was crushed, it was sieved through a 20-mesh sieve, ball-milled at 450 rpm for 5 h, and sieved again through a 300-mesh sieve to obtain a composite glass powder;
[0032] S2: 18 g of dimethyl monochlorosilane, 1.1 g of vinyl trichlorosilane, 0.5 g of chloroplatinic acid, and 5 g of deionized water were added to 50 g of ether, heated to 40° C. for reaction for 4 h, and vacuumed at 120° C. to remove ether and water, and 13 g of acrylic acid was added, and the mixture was kept at 120° C. for reaction for 4 h under a nitrogen atmosphere to obtain a carboxyl-terminated hyperbranched polysiloxane;
[0033] S3: 6 g of carboxyl-terminated hyperbranched polysiloxane, 5 g of urea and 0.2 g of antimony trioxide were mixed uniformly, heated to 145°C and 0.1 MPa vacuum for 1 h, heated to 170°C, 190°C, 210°C and 230°C at a heating rate of 5°C / min, respectively, kept warm for 30 min, 30 min, 30 min and 2 h, and cooled to obtain amide-terminated hyperbranched polysiloxane;
[0034] S4: After the surface of 1g of composite glass powder is acidified, it is washed, dried, and ultrasonically dispersed in ether, 1g of terminal amide hyperbranched polysiloxane is added, stirred for reaction, washed, dried, and the dried product is added to 1g of 15wt% chloroplatinic acid ether solution, stirred evenly, and the ether is removed by rotary evaporation to obtain modified glass powder; wherein the acidifying liquid is a compound of phosphoric acid and phytic acid in a mass ratio of 1:1;
[0035] S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10min; add 20g of modified glass powder, 9g of magnesium hydroxide, and 1g of modified triphosphazene flame retardant and mix for 10min; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0036] Example 2: A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid-cooled cable: S1: 19 g of phosphate glass powder and 1 g of cerium oxide were mixed evenly, compacted, and placed in a muffle furnace and heated to 1000°C at a heating rate of 10°C / min for calcination for 30 min to obtain a composite glass block; the composite glass block was crushed, sieved through a 20-mesh sieve, ball-milled at 450 rpm for 5 h, and sieved again through a 300-mesh sieve to obtain a composite glass powder;
[0037] S2: 18 g of dimethyl monochlorosilane, 1.1 g of vinyl trichlorosilane, 0.5 g of chloroplatinic acid, and 5 g of deionized water were added to 50 g of ether, heated to 40° C. for reaction for 4 h, and vacuumed at 120° C. to remove ether and water, and 13 g of acrylic acid was added, and the mixture was kept at 120° C. for reaction for 4 h under a nitrogen atmosphere to obtain a carboxyl-terminated hyperbranched polysiloxane;
[0038] S3: 6 g of carboxyl-terminated hyperbranched polysiloxane, 5 g of urea and 0.2 g of antimony trioxide were mixed uniformly, heated to 145°C and 0.1 MPa vacuum for 1 h, heated to 170°C, 190°C, 210°C and 230°C at a heating rate of 5°C / min, respectively, kept warm for 30 min, 30 min, 30 min and 2 h, and cooled to obtain amide-terminated hyperbranched polysiloxane;
[0039] S4: After the surface of 1g of composite glass powder is acidified, it is washed, dried, and ultrasonically dispersed in ether, 1g of terminal amide hyperbranched polysiloxane is added, stirred for reaction, washed, dried, and the dried product is added to 1g of 15wt% chloroplatinic acid ether solution, stirred evenly, and the ether is removed by rotary evaporation to obtain modified glass powder; wherein the acidifying liquid is a compound of phosphoric acid and phytic acid in a mass ratio of 1:1;
[0040] S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10min; add 20g of modified glass powder, 9g of magnesium hydroxide, and 1g of modified triphosphazene flame retardant and mix for 10min; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0041] Example 3: A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid-cooled cable: S1: 19 g of phosphate glass powder and 1 g of cerium oxide were mixed evenly, compacted, and placed in a muffle furnace and heated to 1000°C at a heating rate of 10°C / min for calcination for 30 min to obtain a composite glass block; the composite glass block was crushed, sieved through a 20-mesh sieve, ball-milled at 450 rpm for 5 h, and sieved again through a 300-mesh sieve to obtain a composite glass powder;
[0042] S2: 18 g of dimethyl monochlorosilane, 1.1 g of vinyl trichlorosilane, 0.5 g of chloroplatinic acid, and 5 g of deionized water were added to 50 g of ether, heated to 40° C. for reaction for 4 h, and vacuumed at 120° C. to remove ether and water, and 13 g of acrylic acid was added, and the mixture was kept at 120° C. for reaction for 4 h under a nitrogen atmosphere to obtain a carboxyl-terminated hyperbranched polysiloxane;
[0043] S3: 6 g of carboxyl-terminated hyperbranched polysiloxane, 5 g of urea and 0.2 g of antimony trioxide were mixed uniformly, heated to 145°C and 0.1 MPa vacuum for 1 h, heated to 170°C, 190°C, 210°C and 230°C at a heating rate of 5°C / min, respectively, kept warm for 30 min, 30 min, 30 min and 2 h, and cooled to obtain amide-terminated hyperbranched polysiloxane;
[0044] S4: After the surface of 1g of composite glass powder is acidified, it is washed, dried, and ultrasonically dispersed in ether, 2g of terminal amide hyperbranched polysiloxane is added, stirred for reaction, washed, dried, and the dried product is added to 1g of 34wt% chloroplatinic acid ether solution, stirred evenly, and the ether is removed by rotary evaporation to obtain modified glass powder; wherein the acidifying liquid is a compound of phosphoric acid and phytic acid in a mass ratio of 1:1;
[0045] S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10min; add 20g of modified glass powder, 9g of magnesium hydroxide, and 1g of modified triphosphazene flame retardant and mix for 10min; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0046] Example 4: A method for preparing a flame-retardant cross-linked irradiated cable material for liquid-cooled cables of charging piles: S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 20g of modified glass powder, 1g of magnesium hydroxide, and 9g of modified triphosphazene flame retardant and mix for 10 minutes; cold press and cross-link by irradiation to obtain a flame-retardant cross-linked irradiated cable material.
[0047] The remaining steps are the same as those in Example 3.
[0048] Example 5: A method for preparing a flame-retardant cross-linked irradiated cable material for liquid-cooled cables of charging piles: S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 20g of modified glass powder, 5g of magnesium hydroxide, and 5g of modified triphosphazene flame retardant and mix for 10 minutes; cold press and cross-link by irradiation to obtain a flame-retardant cross-linked irradiated cable material.
[0049] The remaining steps are the same as those in Example 3.
[0050] Example 6: A method for preparing a flame-retardant cross-linked irradiated cable material for liquid-cooled cables of charging piles: S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 30g of modified glass powder, 5g of magnesium hydroxide, and 5g of modified triphosphazene flame retardant and mix for 10 minutes; cold press and cross-link by irradiation to obtain a flame-retardant cross-linked irradiated cable material.
[0051] The remaining steps are the same as those in Example 3.
[0052] Example 7: A method for preparing a flame-retardant cross-linked irradiated cable material for liquid-cooled cables of charging piles: S5: Add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 25g of modified glass powder, 5g of magnesium hydroxide, and 5g of modified triphosphazene flame retardant and mix for 10 minutes; cold press and cross-link by irradiation to obtain a flame-retardant cross-linked irradiated cable material.
[0053] The remaining steps are the same as those in Example 3.
[0054] Comparative Example 1: A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid-cooled cable: add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 25g of phosphate glass powder, 5g of magnesium hydroxide, and 5g of hexachlorocyclotriphosphazene flame retardant and mix for 10 minutes; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0055] Comparative Example 2: A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid-cooled cable: add 100g of methyl vinyl silicone rubber into a mixer and mix; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10 minutes; add 25g of phosphate glass powder, 5g of magnesium hydroxide, and 5g of modified triphosphazene flame retardant and mix for 10 minutes; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0056] Comparative Example 3: A method for preparing a flame-retardant cross-linked irradiated cable material for liquid-cooled cables of charging piles: S5: Add 100g of methyl vinyl silicone rubber into a mixer and start refining; add 15g of fumed silica, 30g of mica powder, and 2.5g of hydroxy silicone oil in sequence and mix for 10min; add 25g of modified glass powder, 5g of magnesium hydroxide, and 5g of hexachlorocyclotriphosphazene flame retardant and mix for 10min; cold press molding, irradiation cross-linking, and obtain a flame-retardant cross-linked irradiated cable material.
[0057] The remaining steps are the same as those in Example 1.
[0058] Experiment: Limiting oxygen index test: The flame-retardant cross-linked irradiated cable materials prepared in the examples and comparative examples were prepared into 4mm×10mm×100mm rectangular test specimens and tested using a digital oxygen index measuring instrument;
[0059] Mechanical property test: The flame-retardant cross-linked irradiated cable materials prepared in the examples and comparative examples were made into dumbbell-shaped specimens of 25 mm×4 mm×2 mm, and tested using a universal material testing machine according to ASTM D412, with a tensile rate of 50 mm / min;
[0060] Ceramic body mechanical properties test: The flame-retardant cross-linked irradiated cable material prepared in the embodiment and the comparative example was prepared into a strip sample of 80mm×10mm×3mm, placed in a muffle furnace and heated to 1000℃ at a heating rate of 10℃ / min and calcined for 30min to obtain a ceramic body test strip; the test was carried out using a universal testing machine at a test rate of 1mm / min.
[0061] Table Flame retardant cross-linked irradiated cable material performance test data table
[0062]
[0063] Conclusion: The flame retardant cross-linked irradiated cable materials prepared in Examples 1-7 have excellent flame retardant properties compared with the common commercially available solutions in Example 1; only modified flame retardant was used in Example 2, and only modified glass powder was used in Example 3. The technical effects produced by Examples 2 and 3 are far lower than the technical effects of the flame retardant cross-linked irradiated cable materials prepared in Examples 1-7 of the present invention. This is due to the functional effects between the internal components of the flame retardant cross-linked irradiated cable materials prepared in the present invention. The flame retardant cross-linked irradiated cable materials prepared in the present invention have excellent flame retardant properties.
[0064] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable, characterized in that: The following steps are involved: Add methyl vinyl silicone rubber into a mixer and start mixing; add fumed silica, mica powder and hydroxy silicone oil in sequence and mix for 10-30 minutes; add modified glass powder, magnesium hydroxide and modified triphosphazene flame retardant and mix for 10-30 minutes; cold press molding, irradiation cross-linking, and obtain flame-retardant cross-linked irradiated cable material.
2. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 1, characterized in that: The proportions of the components in the flame-retardant cross-linked irradiated cable material, by mass, are 100-120 parts of methyl vinyl silicone rubber, 15-20 parts of fumed silica, 30-40 parts of mica powder, 2.5-3 parts of hydroxy silicone oil, 20-30 parts of modified glass powder, 1-10 parts of magnesium hydroxide, and 1-10 parts of modified triphosphazene flame retardant.
3. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 1, characterized in that: The method for preparing the modified glass powder comprises the following steps: S1: mixing phosphate glass powder and cerium oxide uniformly, compacting, and placing in a muffle furnace for high-temperature calcination to obtain a composite glass block; crushing the composite glass block, sieving, ball milling, and sieving again to obtain a composite glass powder; S2: adding dimethyl monochlorosilane, vinyl trichlorosilane, chloroplatinic acid and deionized water to ether, heating for reaction, removing ether and water by vacuuming under reduced pressure, adding acrylic acid, and keeping the temperature for reaction under nitrogen atmosphere to obtain carboxyl-terminated hyperbranched polysiloxane; S3: uniformly mixing the carboxyl-terminated hyperbranched polysiloxane, urea and antimony trioxide, heating for vacuum reaction, heating for normal pressure reaction, and cooling to obtain an amide-terminated hyperbranched polysiloxane; S4: After the surface of the composite glass powder is acidified, it is ultrasonically dispersed in ether, and terminal amide hyperbranched polysiloxane is added. The reaction is stirred, washed, and dried. The dried product is added to chloroplatinic acid ether solution, stirred evenly, and the ether is removed by rotary evaporation to obtain modified glass powder.
4. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 3, characterized in that: In step S1, the mass ratio of phosphate glass powder to cerium oxide is (18-19):(1-2).
5. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 3, characterized in that: In step S2, the mass ratio of dimethyl monochlorosilane:vinyl trichlorosilane:acrylic acid is (18-20):(1.1-1.3):(13-15).
6. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 3, characterized in that: In step S3, the mass ratio of carboxyl-terminated hyperbranched polysiloxane to urea is 6:(5-10).
7. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 3, characterized in that: In step S4, the mass ratio of the composite glass powder: the amide-terminated hyperbranched polysiloxane: the chloroplatinic acid in the chloroplatinic acid ether solution is 1:(1-2):(0.15-0.34).
8. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 1, characterized in that: The preparation method of the modified triphosphazene flame retardant comprises the following steps: 4-ethoxyphenol, hexachlorocyclotriphosphazene and sodium hydroxide are added to tetrahydrofuran, and refluxed to obtain a cyclophosphazene p-ethoxyphenol derivative; the cyclophosphazene p-ethoxyphenol derivative is added to a dichloromethane solution of boron tribromide, and reacted at room temperature to obtain a cyclophosphazene p-hydroxyphenol derivative; the cyclophosphazene p-hydroxyphenol derivative, allyl bromide and potassium carbonate are added to acetone, and refluxed to obtain the solvent, and the solvent is removed under reduced pressure, washed and dried to obtain a modified triphosphazene flame retardant.
9. The method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to claim 8, characterized in that: In the cyclophosphazene p-ethoxyphenol derivative, the mass ratio of 4-ethoxyphenol: hexachlorocyclotriphosphazene: sodium hydroxide is 1:(2.5-2.58):(0.98-1.02); in the cyclophosphazene p-hydroxyphenol derivative, the mass ratio of cyclophosphazene p-ethoxyphenol derivative: boron tribromide is (2.2-2.28):(1.64-1.7); in the modified triphosphazene flame retardant, the mass ratio of cyclophosphazene p-hydroxyphenol derivative: allyl bromide: potassium carbonate is (0.8-0.89):(0.72-0.74):(0.84-0.85).
10. The flame-retardant cross-linked irradiated cable material prepared according to the method for preparing a flame-retardant cross-linked irradiated cable material for a charging pile liquid cooling cable according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of cyclophosphazene modified bismaleimide resin
CN105801858A
Ceramic flame-retardant and fire-resistantsilicone rubbercompositematerial and preparation method thereof
CN106832960A
Allyl-phenoxy-cyclophosphazene compound, and production method therefor
CN107614509A
Porcelainizable halogen-free flame-retardant silicone rubber and preparation method thereof
CN110845850A
High-strength flame-retardant cable special material and preparation method thereof
CN112679961A